Proceedings of the 4th ACM Workshop on Digital Rights Management 2004
DOI: 10.1145/1029146.1029157
|View full text |Cite
|
Sign up to set email alerts
|

Software piracy prevention through diversity

Abstract: Software piracy is a major concern for software providers, despite the many defense mechanisms that have been proposed to prevent it. This paper identifies the fundamental weaknesses of existing approaches, resulting from the static nature of defense and the impossibility to prevent the duplication of digital data. A new scheme is presented that enables a more dynamic nature of defense and makes it harder to create an additional, equally useful copy. Furthermore it enables a fine-grained control over the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The type and quality of access to the Internet and its cost affect the access to the software. In [29], [30], using a population (219 professional users and 575 amateur users), software and hardware protection against unauthorized copying of the software was analyzed using a survey. The results showed that none of the protections has a significant impact on the level of theft.…”
Section: E Technical Dimensionsmentioning
confidence: 99%
“…The type and quality of access to the Internet and its cost affect the access to the software. In [29], [30], using a population (219 professional users and 575 amateur users), software and hardware protection against unauthorized copying of the software was analyzed using a survey. The results showed that none of the protections has a significant impact on the level of theft.…”
Section: E Technical Dimensionsmentioning
confidence: 99%
“…While software diversification is an effective solution (see e.g. [2]), it raises major difficulties in software distribution, because each copy has to be different. There is no efficient way for the distribution of diversified copies via physical media (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Another point to note is that the checker structure and location changes with each invocation of the application, providing an ever-changing attack surface for the adversary. Based on the outcomes derived by previous work on software diversity, [11,85,90], we conclude that instantiation polymorphism is effective at defeating automated attacks based on regular expressions. Figure 5.8 displays the performance overhead of Strata and the protection features normalized to native (i.e., the baseline is the application running natively on the platform).…”
Section: Measuring Diversity Of Checker Instancesmentioning
confidence: 67%
“…Since automated attacks are easier to craft than customized attacks, the vulnerability of any security scheme to automated attacks significantly reduces its effectiveness. To combat such attacks, many systems employ software diversity, which consists of customizing every instance of a particular security scheme [85,86] . The basic premise behind software diversity is that each security implementation is different from another instance, such that an automatic attack has a reduced chance of success.…”
Section: Instantiation Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation